La Serna, Miguel. With Masses and Arms. Peru’s Túpac Amaru Revolutionary Movement. Chapel Hill: The University of North Carolina Press, 2020. - García Rodríguez, Ileana (Latinoamérica. Revista de Estudios Latinoamericanos, 2023)
Reseña del libro: La Serna, Miguel. With Masses and Arms. Peru’s Túpac Amaru Revolutionary Movement. Chapel Hill: The University of North Carolina Press, 2020.